2019
DOI: 10.3390/ijerph16091542
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Affecting Traffic Accidents at Urban Weaving Sections: Evidence from China

Abstract: As a critical configuration of interchanges, the weaving section is inclined to be involved in more traffic accidents, which may bring about severe casualties. To identify the factors associated with traffic accidents at the weaving section, we employed the multinomial logistic regression approach to identify the correlation between six categories of risk factors (drivers’ attributes, weather conditions, traffic characteristics, driving behavior, vehicle types and temporal-spatial distribution) and four types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 56 publications
0
18
0
3
Order By: Relevance
“…Drivers tend to change lanes while trying to merge from on-ramp to freeway and diverge from freeway to off-ramp in the type-A weaving sections causing sideswipe crashes. Lane change was an important factor affecting sideswipe crashes (Mao et al, 2019). On other hand, sideswipe crashes per hour decrease as width of inside shoulder increases.…”
Section: Rear-end Crashesmentioning
confidence: 98%
See 1 more Smart Citation
“…Drivers tend to change lanes while trying to merge from on-ramp to freeway and diverge from freeway to off-ramp in the type-A weaving sections causing sideswipe crashes. Lane change was an important factor affecting sideswipe crashes (Mao et al, 2019). On other hand, sideswipe crashes per hour decrease as width of inside shoulder increases.…”
Section: Rear-end Crashesmentioning
confidence: 98%
“…Non-weaving volume was considered equal to the freeway volume prior entering the weaving section minus the off-ramp AADT. Weaving ratio was defined as the percentage of the weaving vehicles out of the total number of the inflow vehicles to the section (Mao et al 2019), which is calculated using equation (1).…”
Section: Geometric and Traffic Characteristicsmentioning
confidence: 99%
“…Lebar dan panjang jalinan dapat dilihat pada Gambar 2. C = 135 x Ww 1,3 x (1 + (We/Ww) 1,5 x (1pw/3) 0,5 x (1 + Ww/Lw) -1,8 x Fcs x Frsu [8] melakukan penelitian mengenai faktor resiko penyebab kecelakaan di segmen jalinan menghasilkan kepadatan lalu lintas ≥31 kendaraan/100 m memiliki resiko tertinggi kecelakaan ujung belakang, rasio jalinan ≥ 41% memiliki peluang terbesar kecelakaan dari samping. Cai,Q., Saad, M., Abdel-Aty, M., dan Yuan, J., [9] menggunakan simulasi VISSIM untuk mengetahui panjang jalinan optimal berkaitan dengan aspek keselamatan di jalan bebas hambatan, menghasilkan panjang optimal setiap pergantian lajur (LLC) adalah 1000 kaki memberikan kinerja keselamatan lalu lintas terbaik dengan tingkat konflik terendah.…”
Section: Jalinanunclassified
“…Previous studies have revealed that a large percentage of motor vehicle traffic accidents are caused by drivers [2][3][4]. Therefore, research on drivers' driving behavior has always been a hot spot in the field of road traffic safety [5].…”
Section: Introductionmentioning
confidence: 99%